2006
DOI: 10.1523/jneurosci.3364-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identified Motoneurons Involved in Sexual and Eliminative Functions in the Rat Are Powerfully Excited by Vasopressin and Tachykinins

Abstract: The pudendal motor system is constituted by striated muscles of the pelvic floor and the spinal motoneurons that innervate them. It plays a role in eliminative functions of the bladder and intestine and in sexual function. Pudendal motoneurons are located in the ventral horn of the caudal lumbar spinal cord and send their axon into the pudendal nerve. In the rat, binding sites for vasopressin and tachykinin are present in the dorsomedial and dorsolateral pudendal nuclei, suggesting that these neuropeptides may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 64 publications
(73 reference statements)
1
21
0
Order By: Relevance
“…VPA has relatively weak selectivity over V 1B R and oxytocinR (20). Because a highly selective V 1A R antagonist was not available for the intrathecal injection in our study, selective agonists for other vasopressin receptors were applied to confirm the responsible receptor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…VPA has relatively weak selectivity over V 1B R and oxytocinR (20). Because a highly selective V 1A R antagonist was not available for the intrathecal injection in our study, selective agonists for other vasopressin receptors were applied to confirm the responsible receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that V 1A R is responsible for the AVP-induced increase in urethral resistance. Ogier et al (20) indicated that the cultured motor neurons from Onuf's nucleus in neonatal rats can be potently excited by AVP. They showed that the excitation was mediated by V 1A R but not by V 1B R, V 2 R, or oxytocinR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations